Implementation of Abraham Maslow's Humanistic Learning Theory in the Learning Process - Abdul Rahman; Nurfarida Deliani; Juliana Batubara; Rahmat Rahmat; Samsurizal Samsurizal; M. Hidayat Ediz (Sekolah Tinggi Agama Islam Pengembangan Ilmu Al-Qur`an Sumatera Barat, 2023)
This research aims to examine the implementation of Abraham Maslow's humanistic learning theory in the learning process. The method used in this research is the Systematic Literature Review (SLR) method. This research data uses the main source of information by analyzing documents related to Abraham Maslow's Humanistic learning theory in the learning process. The research results show that the implementation of Abraham Maslow's humanistic learning theory is very relevant to the learning process where there are five human needs that can be applied in the learning process, namely: first, physiological needs where parents must pay attention to children starting from nutrition and other needs because this will relate to development a child; second, the need for safety and security where educators such as parents and teachers must provide a sense of security and safety for children; third, the need to be loved and loved, where the need to love and have someone, parents must create good closeness to their children and a teacher must provide motivation; fourth, the need to be respected. In the learning process, every effort made by students should be respected and the attitude must be equal to all children and there should be no favoritism between students because each child has their own strengths; fifth, the need to increase self-actualization where in implementing humanistic learning theory students are given the opportunity to actualize themselves according to their talents and interests.